ANALYSIS OF PUBLIC SECTOR MANAGEMENT ACCOUNTING SYSTEM IN SUB-DISTRICT OFFICE MANTIKULORE, PALU CITY - Ade Ainun Ariyanti; Fadhilla Septiani; Merinda Anisa; Ernawaty Usman; Abdul Pattawe; Sugianto (RADJA PUBLIKA, 2026)
This study aims to analyze the implementation of a management accounting system in the public sector, specifically at the Mantikulore Village Office. The study used a qualitative approach with descriptive methods through observation, interviews, and documentation. The results indicate that the management accounting system has been implemented, but is not yet optimal, particularly in aspects of information timeliness, data integration, and the use of information technology. Furthermore, the main obstacles faced include limited human resources and weak internal control systems. Therefore, strengthening technology-based information systems and increasing human resource capacity are necessary to improve accountability and public service performance.